ELECTROSPUN NANOFIBERS FROM CU2O NANOPARTICLES AND CELLULOSE ACETATE (Journal of Sciences & Technology, 2017)
Polyol synthesis of cuprous oxide Cu2O nanoparticles was carried out by reducing CuCl2.2H2O with sodium hydroxide in the presence of Diethylene glycol (DEG) as a solvent and capping agent. These Cu2O nanoparticles were reinforced in cellulose acetate (CA) matrix by electrospinning of CA/ Cu2O in N-Ndimethyl formamid and composite nanofibrous were synthesized. The effect of nanoparticles concentration on the thermal behavior of the resultant fibrous was examined by means of differential scanning calorimetric (DSC) and infrared spectroscopy (FTIR). Also the influence of nanoparticles on the size and morphology of the nanofibers was examined by scanning electron microscopy (SEM).